1996
DOI: 10.5089/9781451852097.001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Corruptionon Growth, Investment, and Government Expenditure

Abstract: This is a Working Paper and the author(s) would welcome any comments on the present text. Citations should refer to a Working Paper of the International Monetary Fund, mentioning the authoi(s), and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
175
2
29

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(217 citation statements)
references
References 15 publications
11
175
2
29
Order By: Relevance
“…The point of departure of this line of work is Shleifer and Vishny (1993) who argue that corrupt governments will tend to favor infrastructure and defense projects where corruption opportunities are abundant (compared to spending on say, education and health). The empirical evidence is largely supportive of this since corrupt countries tend to overinvest in public infraestructures which moreover are of lower quality (Tanzi and Davoodi 1997), spend more on defense (Gupta, de Mello and Sharan 2001) and less on education (Mauro 1997 and1998). More recently, Liu and Mikesell (2014) draw on evidence across U.S. states and report that corruption increases spending in public construction projects and reduces spending on education and health.…”
Section: Construction and Corruption: Existing Evidencementioning
confidence: 94%
See 1 more Smart Citation
“…The point of departure of this line of work is Shleifer and Vishny (1993) who argue that corrupt governments will tend to favor infrastructure and defense projects where corruption opportunities are abundant (compared to spending on say, education and health). The empirical evidence is largely supportive of this since corrupt countries tend to overinvest in public infraestructures which moreover are of lower quality (Tanzi and Davoodi 1997), spend more on defense (Gupta, de Mello and Sharan 2001) and less on education (Mauro 1997 and1998). More recently, Liu and Mikesell (2014) draw on evidence across U.S. states and report that corruption increases spending in public construction projects and reduces spending on education and health.…”
Section: Construction and Corruption: Existing Evidencementioning
confidence: 94%
“…Among its mainy ills, economists have reported that corruption tends to reduce economic growth (Knack and Keefer 1995;Mauro 1997;Tanzi and Davoodi 2001), increase income and educational inequalities (Gupta et al 2002), reduce spending on health and education (Mauro 1998;Gupta, Davoodi and Tiongson 2001) and enlarge the underground economy thus reducing government revenues (Johnson et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Bahmani-Oskooee and Goswami (2005) find that black market premium is higher in countries that are plagued by more corruption. De la Croix and Delavallade (2009), Tanzi and Davoodi (1997), and Mauro (1997) argue that corruption distorts public expenditures in favor of specific types of spending for which rent-seeking is easier and better concealed. Murphy et al (1991Murphy et al ( , 1993 argue that it drives potential entrepreneurs to rent-seeking activities, or even to becoming corrupt officials themselves.…”
Section: Review Of Corruption Literaturementioning
confidence: 99%
“…The few 1 See Méndez and Sepúlveda (2006) for more details on these indexes. Other examples that use these indexes include Mauro (1995Mauro ( , 1997, Gupta, et al (2001), and Paldam (2002). See also the studies published in the four-volume set on The Politics of Corruption, edited by and , which also include several empirical studies.…”
Section: Introductionmentioning
confidence: 99%